Pedagogia da terra: significados da formação para educadores e educadoras do campo - Tatyanne Gomes Marques (2010)
This research, entitled "Pedagogia da Terra: Meanings from Rural Educators about their Teacher Education Program, aimed to interpret the meanings assigned by rural educators to the Pedagogia da Terra Teacher Education Program, developed in Satate University of Bahia (UNEB) at campus of Bom Jesus da Lapa. The used concept of meanings adopted in this thesis implied to understand not only the meanings themselves the most recurrent in the statements of the interviewees but also their reason. Therefore, we looked for stablishing a causal connection between the proposal of this Teacher Education Program, object of this research, and rural education linked to the political and pedagogical project of social movements that struggle for land reform. The requested approach was based, then on the qualitative tenets of the research. Questionnaires and semi-structured interviews, as document analysis to characterize and contextualize the course plan were used. Through dialogue with authors that also discuss the theme, including Arroyo (2004, 2007, 2008, 2010), Caldart (1996, 1997, 2000, 2002, 2004, 2008), Diniz-Pereira (2004, 2008), Fernandes (2004),Molina (2009, 2010), Lins (2006) and through the procedures used in data analysis, it was possible to interpret the meanings assigned by rural educators to Pedagogia da Terra Teacher Education Program are personal, technical and professional; and, political/ideological. These meanings, recurrent in the interviewees statements, are linked, asevidenced by the data, to the experiences of these educators, especially to their activism in social movements to which they belong